Spinal movement and dural sac compression during airway management in a cadaveric model with atlanto-occipital instability - Liao, Shiyao; Schneider, Niko; Weilbacher, Frank; Stehr, Anne; Matschke, Stefan; Grützner, Paul Alfred; Popp, Erik; Kreinest, Michael (European spine journal, 2018)
Purpose: To analyze the compression of the dural sac and the cervical spinal movement during performing different airway interventions in case of atlanto-occipital dislocation. Methods: In six fresh cadavers, atlanto-occipital dislocation was performed by distracting the opened atlanto-occipital joint capsule and sectioning the tectorial membrane. Airway management was done using three airway devices (direct laryngoscopy, video laryngoscopy, and insertion of a laryngeal tube). The change of dural sac’s width and intervertebral angulation in stable and unstable atlanto-occipital conditions were recorded by video fluoroscopy with myelography. Three-dimensional overall movement of cervical spine was measured in a wireless human motion track system. Results: Compared with a mean dural sac compression of − 0.5 mm (− 0.7 to − 0.3 mm) in stable condition, direct laryngoscopy caused an increased dural sac compression of − 1.6 mm (− 1.9 to − 0.6 mm, p = 0.028) in the unstable atlanto-occipital condition. No increased compression on dural sac was found using video laryngoscopy or the laryngeal tube. Moreover, direct laryngoscopy caused greater overall extension and rotation of cervical spine than laryngeal tube insertion in both stable and unstable conditions. Among three procedures, the insertion of a laryngeal tube took the shortest time. Conclusion: In case of atlanto-occipital dislocation, intubation using direct laryngoscopy exacerbates dural sac compression and may cause damage to the spinal cord.